Lycopene in protection against obesity and diabetes: A mechanistic review. (September 2020) - Zhu, Ruyuan; Chen, Beibei; Bai, Ying; Miao, Tianyi; Rui, Li; Zhang, Hao; Xia, Bingke; Li, Yu; Gao, Sihua; Wang, Xiang-Dong; Zhang, Dongwei
Graphical abstract: Abstract: Lycopene, a natural pigment that mainly exists in the mature fruit of tomatoes, has gained increasing attention due to its protective effects against obesity and diabetes. The aim of this review is to summarize the potential mechanisms in which lycopene exerts protection against obesity and diabetes, along with highlighting its bioavailability, synthesis and safety. Literature sources used in this review were from the PubMed Database, China Knowledge Resource Integrated Database, China Science and Technology Journal Database, National Science and Technology Library, Wanfang Data, and the Web of Science. For the inquiries, keywords such as lycopene, properties, synthesis, diabetes, obesity, and safety were used in various combinations. About 200 articles and reviews were evaluated. Lycopene exhibits anti-obesity and anti-diabetic activities in different organs and/or tissues, including adipose tissue, liver, kidney, pancreas, brain, ovaries, intestine, and eyes. The underlying mechanism may be attributed to its anti-oxidant and anti-inflammatory properties and through its ability to regulate of AGE/RAGE, JNK/MAPK, PI3K/Akt, SIRT1/FoxO1/PPARγ signaling pathways and AchE activity. The epidemiological investigations support that lycopene consumption may contribute to lowering the risk of obesity and diabetes. The cis -isomers of lycopene are more bioavailable and better absorbed than trans -lycopene, and mainly distribute in liver and adipose tissue. Lycopene exhibits a good margin of safety and can be obtained by plant extraction, chemical synthesis and microbial fermentation. In summary, lycopene consumption beneficially contributes to protecting against diabetes and obesity in animal studies and epidemiological investigations, which supports the potential of this compound as a preventive/therapeutic agent against these disorders. Well-designed, prospective clinical studies are warranted to evaluate the potential therapeutic effect of lycopene against common metabolic diseases.